Implementation of Coaching in the Change Action Agenda for Supervisory Leadership Training (PKP) Participants in 2021 at the Human Resources Development Agency of Jambi Province - Eti Fitriani (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2021)
In the implementation of Supervisory Leadership Training (PKP), the role of Widyaiswara is not only limited to being a teacher or facilitator but also plays a role as a coach in guiding Action for Change. Action for Change is a working paper for PKP participants whose assessment weight reaches 50 (fifty) percent of the total final score of the participants. In order for participants to get the expected results when participating in the training, the coach is expected to be able to carry out his role to the maximum, starting from the preparation of the change action plan, the implementation process in the workplace, and during the preparation of the change action report. Seeing the importance of this, in this study, the author will try to describe how the coaching process is carried out by coaches and analyze it by comparing it with theories about coaching and regulations issued by LAN regarding morning coaching for PKP participants. Field findings show that the coaching process is in accordance with LAN requirements, the coaches have carried out their role as coaches to explore the potential of participants and provide guidance, motivating participants from the beginning of the mentoring process and when they face obstacles in the field, but when compared with theory-based -The specific skills needed to become a reliable coach, still need development efforts through activities, workshops/training to improve the coaching skills of Widyaiwaras in Jambi Province, which are expected to have an impact on improving the quality of action results changes in PKP participants at BPSDM Jambi Province.